Developing English Website for Customer Service of Best Gym Malang - Salsabila, Tiara Devina; Handayani, Tri Astuti; Agustina, Hiqma Nur (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
Small and Medium-sized Enterprises (SMEs) in the fitness industry play a vital role in economic growth but often face challenges in market visibility and operational efficiency. This research focuses on developing an English-language website for Best Gym Malang to improve its customer service, accessibility, and reach. Using the ADDIE model, the research followed a structured process: Analysis, Design, Development, Implementation, and Evaluation. The website provides detailed information about the gym's services, facilities, membership options, and schedules. Field testing with 40 respondents revealed that 50% strongly agreed the website was comprehensive and engaging, with features enhancing user satisfaction and driving action. The study concludes that the website effectively addresses customer needs, boosts engagement, and positions the business for digital growth.